Mechanisms of seed ageing under different storage conditions for Vigna radiata (L.) Wilczek: Lipid peroxidation, sugar hydrolysis, Maillard reactions and their relationship to glass state transition - Murthy, U.M.N. (2014)
10.1093/jxb/erg092